Tacrolimus ameliorates tubulointerstitial inflammation in diabetic nephropathy via inhibiting the NFATc1/TRPC6 pathway. Issue 17 (11th August 2020) - Zhang, Shumin; Wang, Huafen; Liu, Yifei; Yang, Wenxia; Liu, Jialu; Han, Yuzhang; Liu, Yu; Liu, Fuyou; Sun, Lin; Xiao, Li
Abstract: Tubulointerstitial inflammation is crucial for the progression of diabetic nephropathy (DN), and tubular cells act as a driving force in the inflammatory cascade. Emerging data suggested that tacrolimus (TAC) ameliorates podocyte injury and macrophage infiltration in streptozotocin (STZ) mice. However, the effect of TAC on tubulointerstitial inflammation remains unknown. We found that albuminuria and tubulointerstitial damage improved in db/db mice treated with TAC. Macrophage infiltration and expression of IL‐6, TNF‐α, fibronectin, collagen 1 and cleaved caspase 3 were inhibited as well. In addition, the expression of nuclear factor of activated T cell 1 (NFATc1) and transient receptor potential channel 6 (TRPC6) was up‐regulated in the kidneys of DN patients and correlated with tubular injury and inflammation. The expression of NFATc1 and TRPC6 also increased in the kidneys of db/db mice and HK‐2 cells with high glucose (HG), while TAC inhibited these effects. HG‐induced inflammatory markers and apoptosis were reversed by TAC and NFATc1 siRNA in HK‐2 cells, which was abolished by TRPC6 plasmid. Furthermore, HG‐induced TRPC6 expression was inhibited by NFATc1 siRNA, while NFATc1 nuclear translocation was inhibited by TAC, but was restored by TRPC6 plasmid in HK‐2 cells under HG conditions. These findings suggest that TAC ameliorates tubulointerstitial inflammation in DN through NFATc1/TRPC6 feedback loop.